Inclusive Information and Communication Technologies for People with Disabilities - Jenifer Simpson (Disability Studies Quarterly, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:8.5in 11.0in; margin:1.0in 1.25in 1.0in 1.25in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–>Information and Communications Technology (ICT) has the potential both to enhance access for people with disabilities and to contribute to creating barriers. What we now call the digital divide actually began long before the introduction of computers – barriers have existed and still exist today with telephones, television, the Internet and other information technology. It is important to remember that people with disabilities have many different accessibility needs and that there are different ways to make technology accessible and that new accessibility needs emerge as technology changes. This paper looks at the state of accessibility policy in the U.S. in several technology infrastructures that may provide some lessons and directions for increasing inclusive information and communication technologies worldwide. For instance, if the many provisions involving technology in the UN Convention on the Rights of Persons with Disabilities are to have real and substantive meaning, policy and implementation at the infrastructure level must occur.